Delayed apoptosis of buffalo neutrophil during mastitis and metritis - Uppal, Chirag; Kumar, BV Sunil; Deka, Dipak; Verma, Ramneek; Sethi, R S (Indian Journal of Dairy Science, 2022)
Mastitis and metritis are the common inflammatory diseases of buffalo and result huge economic losses to the small-scale farmers. Neutrophils are recruited during inflammation and cleared from site of inflammation by apoptosis to prevent further tissue damage. However, data are lacking on this aspect in buffalo. Hence, the study was aimed to determine the viability and apoptosis of neutrophils of buffalo during mastitis and metritis. Peripheral blood samples were collected from healthy, mastitis and metritis group (n=5, each group). Neutrophils were isolated and maintained up to 48 hr in RPMI-1640. The viability of neutrophils at different time intervals (6, 12, 24, 36 and 48 hr) was determined using trypan blue dye exclusion method. DNA Laddering, light microscopy, caspase-3 and caspase-9 colorimetric assays were used to observe the apoptosis. Freshly isolated neutrophils showed â‰¥ 97% purity and â‰¥ 92% viability. Healthy group showed decrease (p<0.05) in viable neutrophils 12hr and onwards post-incubation. The number of apoptotic neutrophils was lower (p<0.05) at 36hr and onwards post-incubation in mastitis group and at 48hr post-incubation in metritis group as compared to control group. DNA fragmentation was observed after 24hr post-incubation in healthy group and was absent in mastitis and metritis groups suggesting the delayed apoptosis during mastitis and metritis. Caspase-3 and caspase-9 activity did not show any change in healthy group, however, there was significant increase at 24hr and 36hr post-incubation in mastitis and metritis group. Taken together, data suggest delayed apoptosis in mastitis and metritis.